Efektivitas Penerapan Supply Chain Management, Efisiensi Biaya Operasional Pada Kinerja Perusahaan di Moderasi Keunggulan Kompetitif - Siburian, Deddy Suhendra Martua; Hidayati, Siti Aisyah; Pituringsih, Endar (E-Jurnal Akuntansi; Vol 32 No 5 (2022)DO - 10.24843/EJA.2022.v32.i05.p16, 2022)
This study aims to analyze the effect of the effectiveness of the implementation of supply chain management and operational cost efficiency on the company's performance with competitive advantage as a moderating variable. The research population is the decision maker on the CV. Eight Eight as many as 36 people. The results showed that the effect of the effectiveness of the implementation of supply chain management and operational cost efficiency had a positive effect on company performance. Meanwhile, competitive advantage weakens the effect of the effectiveness of implementing supply chain management and operational cost efficiency on company performance. Keywords: Supply Chain Management Effectiveness; Operational Cost Efficiency; Company Performance; Competitive Advantage.